Method for removing oxidation layer of crack fracture of P92 seamless steel pipe

Through laser cleaning and electrochemical reaction of adding sodium nitrite to hydrochloric acid solution, the fracture oxide layer of P92 seamless steel pipe was successfully removed, solving the problem of the original fracture morphology being covered, and an effective analysis of fracture properties and defects was achieved.

CN119804522APending Publication Date: 2025-04-11INNER MONGOLIA NORTH HEAVY INDS GROUP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411983453.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove the fracture oxide layer of P92 seamless steel pipe, resulting in the original crack morphology being covered and it is difficult to perform failure analysis.

Method used

The oxide layer was removed by laser cleaning technology, and then sodium nitrite corrosion inhibitor was added to the hydrochloric acid solution. The oxide layer was gradually peeled off through electrochemical reactions to ensure that the original morphology of the fracture was not damaged.

Benefits of technology

The oxide layer is removed without damaging the original morphology of the fracture, and can effectively analyze the fracture properties and internal defects of the P92 seamless tube, supporting technical support for failure analysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119804522A_ABST
    Figure CN119804522A_ABST
Patent Text Reader

Abstract

The invention discloses a method for removing a P92 seamless steel pipe crack fracture oxide layer, which comprises the following steps: scanning a P92 crack fracture sample by aligning a scanning head of a laser cleaning machine to a P92 sample fracture oxide layer, so that the surface oxide layer of the sample falls off, and the secondary surface layer looses; a hydrochloric acid solution is prepared, a sodium nitrite corrosion inhibitor is added into the hydrochloric acid solution, the volume ratio of the sodium nitrite corrosion inhibitor to hydrochloric acid is 1: 3-1: 5, and the hydrochloric acid solution is poured into an acid-corrosion-resistant vessel; fixing the oxidized fracture surface of the P92 sample subjected to laser cleaning on a bracket downwards, enabling the oxidized fracture surface to be completely immersed in a hydrochloric acid solution, and observing the color of the immersed hydrochloric acid solution until the solution becomes light blue; and after soaking is finished, washing with clear water, soaking in an acetone solution, and cleaning in absolute ethyl alcohol by utilizing ultrasonic oscillation. According to the method, the observation of the original morphology of the fracture of the P92 seamless tube crack failure analysis can be met, and a necessary test basis is provided for technicians.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material failure analysis, and in particular relates to a method for removing an oxide layer on a crack fracture of a P92 seamless steel pipe. Background Art

[0002] Fracture analysis is an important means of failure analysis of metal materials. Whether the original morphology of the fracture can be intuitively presented under an electron microscope is crucial to material fracture analysis. Once the crack is corroded by environmental media, oil pollution, high-temperature oxidation and other factors, a scale layer is formed on the fracture surface, and the internal morphology of the crack is covered. When sampling and analyzing the crack morphology, it no longer has the original characteristics.

[0003] P92 seamless steel pipe is a high-temperature resistant steel pipe. Due to the addition of heat-resistant alloy elements tungsten and molybdenum in production, the ductility of the metal is reduced. When the process design is unreasonable or the execution process deviates, hot processing is prone to cracks and oxidation. When samples are taken along the crack area and the fracture surface is covered with a dense accumulation layer.

[0004] like Figure 1 The figure shows the microscopic observation effect of cleaning the oxide layer on the fracture of P92 seamless pipe in the prior art.

[0005] After cleaning with carbon tetrachloride, petroleum ether, alcohol and other reagents using an ultrasonic oscillator, the original shape of the crack could no longer be recognized under scanning electron microscopy.

[0006] How to use technical means to clean the fracture surface and ensure that its original fracture morphology is not destroyed has always troubled failure analysis technicians. Therefore, it is necessary to study a test method that can remove the fracture accumulation layer and ensure that the original fracture morphology does not need to be destroyed. Summary of the invention

[0007] The purpose of the present invention is to provide a method for removing the oxide layer on the crack fracture of a P92 seamless steel pipe, which solves the problem of difficulty in analyzing the original morphology of crack formation and expansion, can meet the observation of the original morphology of the fracture of the P92 seamless pipe crack failure analysis, and provide necessary experimental basis for technicians.

[0008] To achieve the above purpose, the technical solution used in the present invention is:

[0009] The method for removing the oxide layer of the crack fracture of P92 seamless steel pipe comprises:

[0010] Select the P92 crack fracture specimen to be analyzed, the size of which should not exceed 60mm×60mm×30mm, the fracture surface should not be damaged, and the upper and lower parallel surfaces of the fracture should be flat;

[0011] Laser cleaning technology is used. The scanning head of the laser cleaning machine is aimed at the oxide layer of the fracture of the P92 sample to scan, so that the oxide layer on the surface of the sample falls off and the sub-surface becomes loose.

[0012] Prepare a hydrochloric acid solution with a volume ratio of 5%-10%; the solute hydrochloric acid is analytical grade with a mass fraction of 36%-38%, industrial water can be used, and sodium nitrite corrosion inhibitor is added to the hydrochloric acid solution, the volume ratio of sodium nitrite corrosion inhibitor to hydrochloric acid is 1:3-1:5, and the hydrochloric acid solution is poured into an acid-resistant container;

[0013] Fix the oxidized fracture surface of the laser-cleaned P92 sample on the bracket with the surface facing downward, place the vessel containing the hydrochloric acid solution at the center of the bottom of the bracket, adjust the height of the sample so that the oxidized surface of the fracture is completely immersed in the hydrochloric acid solution for 5 to 10 hours, and observe the color of the hydrochloric acid solution until the solution turns light blue;

[0014] After soaking, remove the P92 seamless pipe sample from the bracket, rinse with water for 1 minute to 2 minutes, soak in acetone solution for 0.5 hour to 1 hour, take out the sample from the acetone solution, put it in anhydrous ethanol and clean it with ultrasonic vibration for 5 minutes to 10 minutes, and blow dry.

[0015] Furthermore, laser cleaning technology is used with an output power of 50W-100W, an optical fiber length of 3-5m, a cleaning scan width of 10mm-100mm, and the laser cleaning machine scanning head is aimed at the oxide layer of the P92 sample fracture and scanned for 30 seconds to 60 seconds, so that the oxide layer on the surface of the sample falls off and the sub-surface layer becomes loose.

[0016] Furthermore, the volume concentration of the hydrochloric acid solution is 8%, the corrosion inhibitor is the cleaning product detergent, the sample is immersed for 6 hours, and the cross section is immersed 3mm below the liquid surface of the hydrochloric acid aqueous solution. The immersion process is best carried out in a ventilated kitchen, and a small amount of hydrochloric acid solution will evaporate during the immersion process.

[0017] Furthermore, the concentration of the hydrochloric acid aqueous solution is 10%, the immersion time is 6 hours, the clean water is rinsed for 1.5 minutes, the acetone is soaked for 1 hour, and the alcohol ultrasonic shaking cleaning is carried out for 10 minutes.

[0018] Furthermore, after the oxide layer is thinned and loosened by laser cleaning technology, hydrochloric acid solution is used to react electrochemically with the oxide on the metal surface. The Cl- ion product produced is dissolved in the test solution, thereby reducing the Cl- ion product attached to the metal surface. The dissolution reaction duration is controlled under the action of the corrosion inhibitor sodium nitrite in the dissolving solution, so that the dissolution reaction occurs slowly, thereby achieving gradual peeling of the oxide on the metal surface. At the same time, excessive reaction of the original metal at the bottom of the oxide layer with the acid solution is avoided, thereby retaining the original morphology of the metal fracture surface.

[0019] Further, the hydrochloric acid solution was poured into an acid corrosion-resistant container with a liquid level of 15 mm to 20 mm to ensure that the fracture surface of the P92 sample was in full contact with the solution.

[0020] Further, a vessel containing the hydrochloric acid solution is placed at the center of the bottom of the bracket, the height of the sample is adjusted so that the oxidized surface of the fracture is completely immersed in the hydrochloric acid solution, and the limit switch of the bracket is locked to fix it.

[0021] Furthermore, the secondary electron mode of the scanning electron microscope was magnified 1000 times to observe the secondary cracks, metallurgical and casting defects of the fracture after cleaning, and the causes of the fracture were analyzed.

[0022] Furthermore, wire cutting was used to take samples vertically along the fracture surface after the oxide layer was removed. The inspection surface was ground and polished to a mirror state, and the edges connected to the fracture surface were ensured to have no chamfers. The thickness of the residual oxide layer on the edges was measured by observation under a microscope at 500 times magnification.

[0023] Furthermore, the laser output power was 80 W, the optical fiber length was 3 m, the cleaning scan width was 50 mm, and the scanning head of the laser cleaning machine was aimed at the oxide layer of the fracture of the P92 sample for scanning for 45 seconds.

[0024] The technical effects of the present invention include:

[0025] The present invention solves the problem of difficulty in analyzing the original morphology of crack formation and expansion. The test method involves the solution composition ratio required for weak electrochemical corrosion, the time required for continuous corrosion of the surface oxide layer, and the control elements of the test process method, which can meet the observation of the original morphology of the fracture of the P92 seamless pipe crack failure analysis and provide necessary test basis for technical personnel.

[0026] The present invention overcomes the problem that the physical vibration method cannot remove the oxide layer on the fracture surface by cleaning it. The present invention adopts a method of laser cleaning and then immersing the oxide layer on the fracture surface in a hydrochloric acid solution with a prescribed proportion and a corrosion inhibitor added thereto to clean it, so that the oxide layer product becomes thinner and slowly dissolves in the solution until the original fracture morphology of the fracture surface can be observed. This achieves the purpose of judging the fracture properties and internal defects of the P92 seamless pipe, and provides important technical support for failure analysis.

[0027] In the present invention, the sample immersion time can effectively remove the oxide layer without excessively damaging the original fracture morphology of the fracture and can achieve the effect of identifying the fracture. When the immersion solution appears blue during visual observation, it indicates that the oxide layer has fallen off.

[0028] The invention has high popularity and is not only suitable for P92 seamless pipe materials but also can be extended to other steel materials; the cleaning test method is simple and easy to operate; the solution has light corrosion on the original surface of the fractured material and has good oxide layer stripping effect; and the original morphological characteristics of the fractured material are presented. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a microscopic observation effect diagram of cleaning the oxide layer on the fracture of P92 seamless pipe in the prior art;

[0030] Figure 2 This is a microscope observation effect diagram of cleaning the oxide layer of the fracture of cast steel ZG32Mn sample in the prior art;

[0031] Figure 3 This is a rendering of the original appearance of the P92 seamless pipe after the oxide layer is removed from the fracture in the present invention;

[0032] Figure 4 This is a spectrum analysis diagram of the surface composition of the P92 seamless pipe after the oxide layer is removed from the fracture in the present invention;

[0033] Figure 5 This is a microscope observation effect diagram of the fracture of the cast steel ZG32Mn sample after the oxide layer is removed in the present invention. DETAILED DESCRIPTION

[0034] The application can be implemented in a variety of different forms, and is not limited to the examples described herein, and these examples are provided to make the disclosure of the present invention more thoroughly understood and comprehensive. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The following description fully demonstrates specific embodiments of the present invention, and enables those skilled in the art to practice and reproduce.

[0035] The method for removing the oxide layer on the crack fracture of P92 seamless steel pipe is as follows:

[0036] 1. Select the P92 crack fracture specimen to be analyzed, the size of which should not exceed 60mm×60mm×30mm. The processing process should ensure that the fracture surface is not damaged, and the upper and lower parallel surfaces of the fracture should be flat;

[0037] 2. Use laser cleaning technology, with an output power of 50W to 100W, a fiber length of 3m, a cleaning scan width of 10mm to 100mm, and the laser cleaning machine scan head is aimed at the oxide layer of the fracture of the P92 sample for 30 seconds to 60 seconds, so that the oxide layer on the surface of the sample falls off and the sub-surface becomes loose;

[0038] The laser-cleaned P92 sample was placed in anhydrous ethanol solution and mechanically cleaned by ultrasonic vibration to ensure that no attachments remained on the surface of the sample.

[0039] The laser-cleaned P92 sample was placed in anhydrous ethanol solution and mechanically cleaned by ultrasonic vibration to ensure that no attachments remained on the surface of the sample.

[0040] 3. Prepare a hydrochloric acid solution with a volume ratio of 5% to 10%. The solute hydrochloric acid is analytical grade with a mass fraction of 36% to 38%. Industrial water can be used. Sodium nitrite corrosion inhibitor is added to the hydrochloric acid solution. The volume ratio of sodium nitrite corrosion inhibitor to hydrochloric acid is 1:3-1:5.

[0041] The volume concentration of the hydrochloric acid solution is 8%, the corrosion inhibitor is the cleaning product detergent, the sample is immersed for 6 hours, and the cross section is immersed 3mm below the liquid surface of the hydrochloric acid solution. The immersion process is best carried out in a ventilated kitchen, and a small amount of hydrochloric acid solution will evaporate during the immersion process.

[0042] The concentration of hydrochloric acid aqueous solution is 10%, the soaking time is 6 hours, the water rinse is 1.5 minutes, the acetone soak is 1 hour, and the alcohol ultrasonic vibration cleaning is 10 minutes.

[0043] After the oxide layer is thinned and loosened by laser cleaning technology, a 5% to 10% hydrochloric acid aqueous solution is used to react electrochemically with the oxide on the metal surface. The Cl - The ion products dissolve in the test solution, making the Cl attached to the metal surface - The ion products are reduced, and the dissolution reaction time is controlled under the action of the corrosion inhibitor sodium nitrite in the dissolving solution, so that the dissolution reaction occurs slowly, thereby achieving the purpose of gradually stripping off the oxide on the metal surface. At the same time, excessive reaction between the original metal at the bottom of the oxide layer and the acid solution is avoided, and the original morphology of the metal fracture surface is retained.

[0044] 4. Pour the hydrochloric acid solution prepared in the above proportion into an acid-resistant container. The liquid level of the hydrochloric acid should be 15 mm to 20 mm to ensure that the fracture surface of the P92 specimen is in full contact with the solution.

[0045] 5. Prepare the sample holder, fix the oxidized fracture surface of the laser-cleaned P92 sample on the holder with the surface facing downward, place the vessel containing the hydrochloric acid solution at the center of the bottom of the holder, and adjust the height of the sample so that the oxidized surface of the fracture is completely immersed in the hydrochloric acid solution;

[0046] The laser output power was 80W, the optical fiber length was 3m, the cleaning scanning width was 50mm, and the scanning head of the laser cleaning machine was aimed at the oxide layer of the fracture of the P92 sample for 45 seconds.

[0047] The vertical position of the bracket crossbeam is adjustable. Place the vessel containing the hydrochloric acid solution at the center of the bottom of the bracket, adjust the height of the sample so that the oxidized surface of the fracture is completely immersed in the hydrochloric acid solution, and lock the bracket limit switch to fix it.

[0048] 6. The oxidized surface of the fracture of the P92 seamless pipe is soaked in the solution for 5 to 10 hours. At this time, observe the color of the hydrochloric acid solution. Wait until the solution turns light blue, otherwise, soak further;

[0049] 7. After soaking, remove the P92 seamless pipe sample from the bracket, rinse with water for 1 to 2 minutes, soak in acetone solution for 0.5 to 1 hour, take out the sample from the acetone solution, put it in anhydrous ethanol, clean it with ultrasonic vibration for 5 to 10 minutes, and blow it dry.

[0050] like Figure 3 As shown in FIG. 1 , it is the original morphology effect diagram of the P92 seamless pipe fracture after removing the oxide layer in the present invention; Figure 4 As shown, it is the energy spectrum analysis diagram of the surface composition of the P92 seamless pipe after the oxide layer is removed from the fracture in the present invention; Figure 5 The figure shows the effect of microscopic observation on the fracture of the cast steel ZG32Mn sample after the oxide layer is removed in the present invention.

[0051] The above-mentioned laser cleaning plus electrochemical cleaning method can cause a certain degree of peeling of the oxide layer on the fracture of the P92 seamless pipe. The sample after immersion treatment is observed under a scanning electron microscope at a magnification of 500 to 2000 times. The fracture morphology after immersion in hydrochloric acid solution is shown. The oxide layer on the fracture surface falls off, the fracture extension path morphology can be observed, and the fracture nature is identified as brittle quasi-cleavage, thereby achieving the removal of the oxide layer on the fracture of the P92 seamless steel pipe.

[0052] In the preferred embodiment, the secondary electron mode of the scanning electron microscope is magnified 1000 times to observe the secondary cracks, metallurgical and casting defects of the fracture after cleaning, and analyze the cause of the fracture.

[0053] In this preferred embodiment, wire cutting is used to take samples vertically along the fracture surface after the oxide layer is removed. The inspection surface is ground and polished to achieve a mirror state, and it is ensured that the edges connected to the fracture surface have no chamfers. The thickness of the residual oxide layer on the edges is measured by observation with a microscope at 500 times.

[0054] Embodiment 1:

[0055] The method for removing the oxide layer on the fracture of a P92 seamless steel pipe comprises the following steps:

[0056] Step 1: Prepare and select the P92 crack fracture specimen to be analyzed, with a size of 60mm×60mm×30mm. The processing process should ensure that the fracture surface is not damaged and the opposite surface of the fracture should be flat;

[0057] Step 2: Use laser cleaning technology, output power 70W, fiber length 3m, cleaning scan width 60mm, laser cleaning machine scanning head aimed at the P92 sample fracture oxide layer scanning, duration 30 seconds, so that the surface oxide layer of the sample falls off, the sub-surface becomes loose. The laser cleaned P92 sample is placed in anhydrous ethanol solution for ultrasonic vibration mechanical cleaning to ensure that there is no residual attachment on the sample surface.

[0058] Step 3: Prepare 8% hydrochloric acid aqueous solution, the solute hydrochloric acid is analytical grade, and the water can be industrial water, and add sodium nitrite corrosion inhibitor to the hydrochloric acid solution, with a volume ratio of 1:5 to hydrochloric acid. Pour the hydrochloric acid solution into a container, and the hydrochloric acid liquid level is 15mm;

[0059] Step 4: Prepare the sample holder, fix the P92 sample with the oxidized fracture surface facing downward on the holder. The vertical position of the holder crossbeam is adjustable. Place the vessel containing the hydrochloric acid solution at the center of the bottom of the holder. Adjust the height of the sample so that the oxidized fracture surface is completely immersed in the hydrochloric acid solution. Lock the limit switch of the holder to fix it.

[0060] Step 5: After the oxidation surface of the fracture of the P92 seamless pipe has been immersed in the solution for 6 hours, observe the color of the hydrochloric acid solution. When the solution turns light blue, the sample can be removed, otherwise it will be immersed further;

[0061] Step 6: Remove the P92 seamless pipe sample from the bracket, rinse with water for 1 minute, soak it in acetone solution for 1 hour, take out the sample from the acetone solution, put it in anhydrous ethanol and clean it with ultrasonic vibration for 5 minutes, and blow it dry;

[0062] Step 7: Observe the fracture morphology of the sample after immersion treatment under a scanning electron microscope at a magnification of 1500 times. The oxide layer on the fracture surface falls off, and the original fracture extension path morphology can be observed. The fracture nature is identified as brittle quasi-cleavage, and the oxide layer on the fracture of the P92 seamless steel pipe is removed. The energy spectrum component analysis of the fracture surface after the oxide layer is removed shows that oxygen is added to the alloy elements of the P92 seamless pipe, indicating that the residual oxidation products on the fracture of the P92 seamless pipe after cleaning have no negative impact on the fracture morphology analysis.

[0063] Embodiment 2:

[0064] The method of removing the oxide layer on the fracture of P92 seamless steel pipe can be extended to the removal of the oxide layer on the fracture surface of other steel materials. For example, the removal of the oxide corrosion layer on the fracture surface of cast steel ZG32Mn structural parts includes the following steps:

[0065] Step 1: After the cast steel ZG32Mn sample was cleaned by ultrasonic vibration in anhydrous ethanol, it was observed under a scanning electron microscope at 800 times. The original shape of the crack could no longer be identified. Figure 4 As shown, the surface effect of the oxide layer covering the fracture of cast steel ZG32Mn before the implementation of the present invention.

[0066] Step 2: Prepare and select the cast steel ZG32Mn sample to be analyzed, with a size of 20mm×20mm×10mm. The processing process should ensure that the fracture surface is not damaged and the opposite surface of the fracture should be flat;

[0067] Step 3: Use laser cleaning technology, output power 100W, fiber length 3m, cleaning scan width 20mm, laser cleaning machine scanning head aimed at the P92 sample fracture oxide layer scanning, duration 60 seconds, so that the surface oxide layer of the sample falls off, the sub-surface becomes loose. The laser cleaned P92 sample is placed in anhydrous ethanol solution for ultrasonic vibration mechanical cleaning to ensure that there is no residual attachment on the sample surface.

[0068] Step 4: Prepare 10% hydrochloric acid aqueous solution, the solute hydrochloric acid is analytical grade, and industrial water can be used. Sodium nitrite corrosion inhibitor is added to the hydrochloric acid solution, and the volume ratio of sodium nitrite to hydrochloric acid is 1:4. Pour the hydrochloric acid solution into a container, and the hydrochloric acid liquid level is 15mm;

[0069] Step 5: Prepare the sample holder, fix the cast steel ZG32Mn sample on the holder with the fracture surface facing downwards. The vertical position of the holder crossbeam is adjustable. Place the vessel containing the hydrochloric acid solution at the center of the bottom of the holder. Adjust the height of the sample so that the oxidized surface of the fracture is completely immersed in the hydrochloric acid solution. Lock the limit switch of the holder to fix it.

[0070] Step 6: After the oxidized surface of the fracture of the cast steel ZG32Mn sample has been immersed in the solution for 10 hours, observe the color of the hydrochloric acid solution. When the solution turns light blue, the sample can be removed, otherwise it will be immersed further;

[0071] Step 7: Remove the cast steel ZG32Mn sample from the bracket, rinse with water for 1 minute, soak it in acetone solution for 1 hour, take it out of the acetone solution, put it in anhydrous ethanol and clean it with ultrasonic vibration for 10 minutes, and blow it dry;

[0072] Step 8: Observe the fracture morphology of the sample after immersion treatment under a scanning electron microscope at a magnification of 2000 times. The oxide layer on the fracture surface falls off, and the original fracture path morphology can be observed. The fracture nature is identified as brittle cracking along the grain boundary, and the oxide layer on the fracture of cast steel ZG32Mn is removed.

[0073] Embodiment 3:

[0074] The method for removing the oxide layer on the fracture of a P92 seamless steel pipe comprises the following steps:

[0075] Step 1: Prepare and select the P92 crack fracture specimen to be analyzed, with a size of 60mm×60mm×30mm. The processing process should ensure that the fracture surface is not damaged and the opposite surface of the fracture should be flat;

[0076] Step 2: The laser output power is 80W, the fiber length is 3m, the cleaning scan width is 50mm, and the laser cleaning machine scan head is aimed at the oxide layer of the P92 sample fracture and scanned for 45 seconds; the oxide layer on the surface of the sample falls off and the sub-surface becomes loose. The laser-cleaned P92 sample is placed in anhydrous ethanol solution for ultrasonic vibration mechanical cleaning to ensure that there is no residual attachment on the surface of the sample.

[0077] Step 3: Prepare 8% hydrochloric acid aqueous solution, the solute hydrochloric acid is analytical grade, and the water can be industrial water, and add sodium nitrite corrosion inhibitor to the hydrochloric acid solution, with a volume ratio of 1:5 to hydrochloric acid. Pour the hydrochloric acid solution into a container, and the hydrochloric acid liquid level is 15mm;

[0078] Step 4: Prepare the sample holder, fix the P92 sample with the oxidized fracture surface facing downward on the holder. The vertical position of the holder crossbeam is adjustable. Place the vessel containing the hydrochloric acid solution at the center of the bottom of the holder. Adjust the height of the sample so that the oxidized fracture surface is completely immersed in the hydrochloric acid solution. Lock the limit switch of the holder to fix it.

[0079] Step 5: After the oxidation surface of the fracture of the P92 seamless pipe has been immersed in the solution for 6 hours, observe the color of the hydrochloric acid solution. When the solution turns light blue, the sample can be removed, otherwise it will be immersed further;

[0080] Step 6: Remove the P92 seamless pipe sample from the bracket, rinse with water for 1 minute, soak it in acetone solution for 1 hour, take out the sample from the acetone solution, put it in anhydrous ethanol and clean it with ultrasonic vibration for 5 minutes, and blow it dry;

[0081] Step 7: Observe the fracture morphology of the sample after immersion treatment under a scanning electron microscope at a magnification of 1500 times. The oxide layer on the fracture surface falls off, and the original fracture extension path morphology can be observed. The fracture nature is identified as brittle quasi-cleavage, such as Figure 2 The figure shows the surface morphology of the P92 seamless steel pipe after the oxide layer is cleaned, and the oxide layer of the P92 seamless steel pipe is removed. The energy spectrum component analysis of the fracture surface after the oxide layer is removed shows that oxygen is added to the alloy elements of the P92 seamless steel pipe. Figure 3 As shown, it is the energy spectrum line diagram of the surface alloy composition of the P92 seamless steel pipe after the broken oxide layer is cleaned, indicating that the oxidation products remaining on the fracture of the P92 seamless pipe after cleaning have no negative impact on the fracture morphology analysis.

[0082] Embodiment 4:

[0083] The method of removing the oxide layer on the fracture of P92 seamless steel pipe can be extended to the removal of the oxide layer on the fracture surface of other steel materials. For example, the removal of the oxide corrosion layer on the fracture surface of cast steel ZG32Mn structural parts includes the following steps:

[0084] Step 1: After the cast steel ZG32Mn sample was cleaned by ultrasonic vibration in anhydrous ethanol, it was observed under a scanning electron microscope at 800 times. The original shape of the crack could no longer be identified. Figure 4 FIG. 1 shows the surface coverage effect of the oxide layer on the fracture of cast steel ZG32Mn before the implementation of the present invention.

[0085] Step 2: Prepare and select the cast steel ZG32Mn sample to be analyzed, with a size of 20mm×20mm×10mm. The processing process should ensure that the fracture surface is not damaged and the opposite surface of the fracture should be flat;

[0086] Step 3: Use laser cleaning technology, output power 100W, fiber length 3m, cleaning scan width 20mm, aim the laser cleaning machine scanning head at the P92 sample fracture oxide layer scanning for 60 seconds, so that the oxide layer on the sample surface falls off and the sub-surface becomes loose. The laser-cleaned P92 sample is placed in anhydrous ethanol solution for ultrasonic vibration mechanical cleaning to ensure that there is no residual attachment on the sample surface.

[0087] Step 4: Prepare 10% hydrochloric acid aqueous solution, the solute hydrochloric acid is analytical grade, and industrial water can be used. Sodium nitrite corrosion inhibitor is added to the hydrochloric acid solution, and the volume ratio of sodium nitrite to hydrochloric acid is 1:4. Pour the hydrochloric acid solution into a container, and the hydrochloric acid liquid level is 15mm;

[0088] Step 5: Prepare the sample holder, fix the cast steel ZG32Mn sample on the holder with the fracture surface facing downwards. The vertical position of the holder crossbeam is adjustable. Place the vessel containing the hydrochloric acid solution at the center of the bottom of the holder. Adjust the height of the sample so that the oxidized surface of the fracture is completely immersed in the hydrochloric acid solution. Lock the limit switch of the holder to fix it.

[0089] Step 6: Wait for the oxidized surface of the fracture of the cast steel ZG32Mn sample to be immersed in the solution for 6 hours, rinse with water for 1.5 minutes, and observe the color of the hydrochloric acid solution. When the solution turns light blue, the sample can be removed, otherwise it will be immersed further;

[0090] Step 7: Remove the cast steel ZG32Mn sample from the bracket, rinse with water for 1 minute, soak it in acetone solution for 1 hour, take it out of the acetone solution, put it in anhydrous ethanol and clean it with ultrasonic vibration for 10 minutes, and blow it dry;

[0091] Step 8: Observe the fracture morphology of the sample after immersion treatment under a scanning electron microscope at a magnification of 2000 times. The oxide layer on the fracture surface falls off, and the original fracture path morphology can be observed. The fracture nature is identified as brittle cracking along the grain boundary, such as Figure 5 As shown, the surface morphology effect of removing the oxide layer on the fracture of the cast steel ZG32Mn structural member sample of the present invention is achieved, and the oxide layer on the fracture of the cast steel ZG32Mn is removed.

[0092] Embodiment 5:

[0093] The method for removing the oxide layer on the fracture of a P92 seamless steel pipe comprises the following steps:

[0094] Step 1: Prepare and select the P92 crack fracture specimen to be analyzed, with a size of 60mm×60mm×30mm. The processing process should ensure that the fracture surface is not damaged and the opposite surface of the fracture should be flat;

[0095] Step 2: Use laser cleaning technology, output power 50W, fiber length 3m, cleaning scan width 60mm, aim the laser cleaning machine scanning head at the P92 sample fracture oxide layer scanning for 30 seconds, so that the oxide layer on the sample surface falls off and the sub-surface becomes loose. The laser-cleaned P92 sample is placed in anhydrous ethanol solution for ultrasonic vibration mechanical cleaning to ensure that there is no residual attachment on the sample surface.

[0096] Step 3: Prepare 10% hydrochloric acid aqueous solution, the solute hydrochloric acid is analytical grade, and industrial water can be used. Sodium nitrite corrosion inhibitor is added to the hydrochloric acid solution, and the volume ratio of sodium nitrite to hydrochloric acid is 1:4. Pour the hydrochloric acid solution into a container, and the hydrochloric acid liquid level is 20mm;

[0097] Step 4: Prepare the sample holder, fix the P92 sample with the oxidized fracture surface facing downward on the holder. The vertical position of the holder crossbeam is adjustable. Place the vessel containing the hydrochloric acid solution at the center of the bottom of the holder. Adjust the height of the sample so that the oxidized fracture surface is completely immersed in the hydrochloric acid solution. Lock the limit switch of the holder to fix it.

[0098] Step 5: After the oxidation surface of the fracture of the P92 seamless pipe has been immersed in the solution for 8 hours, observe the color of the hydrochloric acid solution. When the solution turns light blue, the sample can be removed, otherwise it will be immersed further;

[0099] Step 6: Remove the P92 seamless pipe sample from the bracket, rinse with water for 1 minute, soak it in acetone solution for 1 hour, take out the sample from the acetone solution, put it in anhydrous ethanol and clean it with ultrasonic vibration for 5 minutes, and blow it dry;

[0100] Step 7: Observe the fracture morphology of the sample after immersion treatment under a scanning electron microscope at a magnification of 1500 times. The oxide layer on the fracture surface falls off, and the original fracture extension path morphology can be observed. The fracture nature is identified as brittle quasi-cleavage, and the oxide layer on the fracture of the P92 seamless steel pipe is removed. The energy spectrum component analysis of the fracture surface after the oxide layer is removed shows that oxygen is added to the alloy elements of the P92 seamless pipe, indicating that the residual oxidation products on the fracture of the P92 seamless pipe after cleaning have no negative impact on the fracture morphology analysis.

[0101] Embodiment 6:

[0102] The method of removing the oxide layer on the fracture of P92 seamless steel pipe can be extended to the removal of the oxide layer on the fracture surface of other steel materials. For example, the removal of the oxide corrosion layer on the fracture surface of cast steel ZG32Mn structural parts includes the following steps:

[0103] Step 1: After the cast steel ZG32Mn sample was cleaned by ultrasonic vibration in anhydrous ethanol, it was observed under a scanning electron microscope at 800 times. The original shape of the crack could no longer be identified. Figure 4 FIG. 1 shows the surface coverage effect of the oxide layer on the fracture of cast steel ZG32Mn before the implementation of the present invention.

[0104] Step 2: Prepare and select the cast steel ZG32Mn sample to be analyzed, with a size of 40mm×40mm×20mm. The processing process should ensure that the fracture surface is not damaged and the opposite surface of the fracture should be flat;

[0105] Step 3: Use laser cleaning technology, output power 100W, fiber length 3m, cleaning scan width 20mm, laser cleaning machine scanning head aimed at the P92 sample fracture oxide layer scanning, duration 50 seconds, so that the surface oxide layer of the sample falls off, the sub-surface becomes loose. The laser cleaned P92 sample is placed in anhydrous ethanol solution for ultrasonic vibration mechanical cleaning to ensure that there is no residual attachment on the sample surface.

[0106] Step 4: Prepare 10% hydrochloric acid aqueous solution, the solute hydrochloric acid is analytical grade, and industrial water can be used. Sodium nitrite corrosion inhibitor is added to the hydrochloric acid solution, and the volume ratio of sodium nitrite to hydrochloric acid is 1:5. Pour the hydrochloric acid solution into a container, and the hydrochloric acid liquid level is 19mm;

[0107] Step 5: Prepare the sample holder, fix the cast steel ZG32Mn sample on the holder with the fracture surface facing downwards. The vertical position of the holder crossbeam is adjustable. Place the vessel containing the hydrochloric acid solution at the center of the bottom of the holder. Adjust the height of the sample so that the oxidized surface of the fracture is completely immersed in the hydrochloric acid solution. Lock the limit switch of the holder to fix it.

[0108] Step 6: After the fracture oxidation surface of the cast steel ZG32Mn sample has been immersed in the solution for 9 hours, observe the color of the hydrochloric acid solution. When the solution turns light blue, the sample can be removed, otherwise it will be immersed further;

[0109] Step 7: Remove the cast steel ZG32Mn sample from the bracket, rinse with water for 1 minute, soak it in acetone solution for 1 hour, take it out of the acetone solution, put it in anhydrous ethanol and clean it with ultrasonic vibration for 10 minutes, and blow it dry;

[0110] Step 8: Observe the fracture morphology of the sample after immersion treatment under a scanning electron microscope at a magnification of 2000 times. The oxide layer on the fracture surface falls off, and the original fracture path morphology can be observed. The fracture nature is identified as brittle cracking along the grain boundary, and the oxide layer on the fracture of cast steel ZG32Mn is removed.

[0111] Embodiment 7:

[0112] The method for removing the oxide layer on the fracture of a P92 seamless steel pipe comprises the following steps:

[0113] Step 1: Prepare and select the P92 crack fracture specimen to be analyzed, with a size of 60mm×60mm×30mm. The processing process should ensure that the fracture surface is not damaged and the opposite surface of the fracture should be flat;

[0114] Step 2: Use laser cleaning technology, output power 70W, fiber length 3m, cleaning scan width 100mm, aim the laser cleaning machine scanning head at the P92 sample fracture oxide layer scanning for 30 seconds, so that the oxide layer on the sample surface falls off and the sub-surface becomes loose. The laser-cleaned P92 sample is placed in anhydrous ethanol solution for ultrasonic vibration mechanical cleaning to ensure that there is no residual attachment on the sample surface.

[0115] Step 3: Prepare 5% hydrochloric acid aqueous solution, the solute hydrochloric acid is analytical grade, and the water can be industrial water, and add sodium nitrite corrosion inhibitor to the hydrochloric acid solution, with a volume ratio of 1:3 to hydrochloric acid. Pour the hydrochloric acid solution into a container, and the hydrochloric acid liquid level is 18mm;

[0116] Step 4: Prepare the sample holder, fix the P92 sample with the oxidized fracture surface facing downward on the holder. The vertical position of the holder crossbeam is adjustable. Place the vessel containing the hydrochloric acid solution at the center of the bottom of the holder. Adjust the height of the sample so that the oxidized fracture surface is completely immersed in the hydrochloric acid solution. Lock the limit switch of the holder to fix it.

[0117] Step 5: After the oxidation surface of the fracture of the P92 seamless pipe has been immersed in the solution for 10 hours, observe the color of the hydrochloric acid solution. When the solution turns light blue, the sample can be removed, otherwise it will be immersed further;

[0118] Step 6: Remove the P92 seamless pipe sample from the bracket, rinse with water for 1 minute, soak it in acetone solution for 1 hour, take out the sample from the acetone solution, put it in anhydrous ethanol and clean it with ultrasonic vibration for 5 minutes, and blow it dry;

[0119] Step 7: Observe the fracture morphology of the sample after immersion treatment under a scanning electron microscope at a magnification of 1500 times. The oxide layer on the fracture surface falls off, and the original fracture extension path morphology can be observed. The fracture nature is identified as brittle quasi-cleavage, and the oxide layer on the fracture of the P92 seamless steel pipe is removed. The energy spectrum component analysis of the fracture surface after the oxide layer is removed shows that oxygen is added to the alloy elements of the P92 seamless pipe, indicating that the residual oxidation products on the fracture of the P92 seamless pipe after cleaning have no negative impact on the fracture morphology analysis.

[0120] Embodiment 8:

[0121] The method of removing the oxide layer on the fracture of P92 seamless steel pipe can be extended to the removal of the oxide layer on the fracture surface of other steel materials. For example, the removal of the oxide corrosion layer on the fracture surface of cast steel ZG32Mn structural parts includes the following steps:

[0122] Step 1: After the cast steel ZG32Mn sample was placed in anhydrous ethanol and ultrasonically cleaned, it was observed under a scanning electron microscope at 800 times magnification. The original shape of the crack could no longer be recognized.

[0123] Step 2: Prepare and select the cast steel ZG32Mn sample to be analyzed, with a size of 20mm×20mm×10mm. The processing process should ensure that the fracture surface is not damaged and the opposite surface of the fracture should be flat;

[0124] Step 3: Use laser cleaning technology, output power 100W, fiber length 3m, cleaning scan width 20mm, laser cleaning machine scanning head aimed at the P92 sample fracture oxide layer scanning, duration 60 seconds, so that the surface oxide layer of the sample falls off, the sub-surface becomes loose. The laser cleaned P92 sample is placed in anhydrous ethanol solution for ultrasonic vibration mechanical cleaning to ensure that there is no residual attachment on the sample surface.

[0125] Step 4: Prepare 10% hydrochloric acid aqueous solution, the solute hydrochloric acid is analytical grade, and industrial water can be used. Sodium nitrite corrosion inhibitor is added to the hydrochloric acid solution, and the volume ratio of sodium nitrite to hydrochloric acid is 1:4. Pour the hydrochloric acid solution into a container, and the hydrochloric acid liquid level is 15mm;

[0126] Step 5: Prepare the sample holder, fix the cast steel ZG32Mn sample on the holder with the fracture surface facing downwards. The vertical position of the holder crossbeam is adjustable. Place the vessel containing the hydrochloric acid solution at the center of the bottom of the holder. Adjust the height of the sample so that the oxidized surface of the fracture is completely immersed in the hydrochloric acid solution. Lock the limit switch of the holder to fix it.

[0127] Step 6: After the oxidized surface of the fracture of the cast steel ZG32Mn sample has been immersed in the solution for 6 hours, observe the color of the hydrochloric acid solution. When the solution turns light blue, the sample can be removed, otherwise it will be immersed further;

[0128] Step 7: Remove the cast steel ZG32Mn sample from the bracket, rinse with water for 1 minute, soak it in acetone solution for 1 hour, take it out of the acetone solution, put it in anhydrous ethanol and clean it with ultrasonic vibration for 10 minutes, and blow it dry;

[0129] Step 8: Observe the fracture morphology of the sample after immersion treatment under a scanning electron microscope at a magnification of 2000 times. The oxide layer on the fracture surface falls off, and the original fracture path morphology can be observed. The fracture nature is identified as brittle cracking along the grain boundary, and the oxide layer on the fracture of cast steel ZG32Mn is removed.

[0130] Embodiment 9:

[0131] The method for removing the oxide layer on the fracture of a P92 seamless steel pipe comprises the following steps:

[0132] Step 1: Prepare and select the P92 crack fracture specimen to be analyzed, with a size of 40mm×40mm×20mm. The processing process should ensure that the fracture surface is not damaged and the opposite surface of the fracture should be flat;

[0133] Step 2: Use laser cleaning technology, output power 90W, fiber length 3m, cleaning scan width 60mm, aim the laser cleaning machine scanning head at the P92 sample fracture oxide layer scanning for 30 seconds, so that the oxide layer on the sample surface falls off and the sub-surface becomes loose. The laser-cleaned P92 sample is placed in anhydrous ethanol solution for ultrasonic vibration mechanical cleaning to ensure that there is no residual attachment on the sample surface.

[0134] Step 3: Prepare 5% hydrochloric acid aqueous solution, the solute hydrochloric acid is analytical grade, and the water can be industrial water, and add sodium nitrite corrosion inhibitor to the hydrochloric acid solution, with a volume ratio of 1:3 to hydrochloric acid. Pour the hydrochloric acid solution into a container, and the hydrochloric acid liquid level is 17mm;

[0135] Step 4: Prepare the sample holder, fix the P92 sample with the oxidized fracture surface facing downward on the holder. The vertical position of the holder crossbeam is adjustable. Place the vessel containing the hydrochloric acid solution at the center of the bottom of the holder. Adjust the height of the sample so that the oxidized fracture surface is completely immersed in the hydrochloric acid solution. Lock the limit switch of the holder to fix it.

[0136] Step 5: After the oxidation surface of the fracture of the P92 seamless pipe has been immersed in the solution for 10 hours, observe the color of the hydrochloric acid solution. When the solution turns light blue, the sample can be removed, otherwise it will be immersed further;

[0137] Step 6: Remove the P92 seamless pipe sample from the bracket, rinse with water for 1 minute, soak it in acetone solution for 1 hour, take out the sample from the acetone solution, put it in anhydrous ethanol and clean it with ultrasonic vibration for 5 minutes, and blow it dry;

[0138] Step 7: Observe the fracture morphology of the sample after immersion treatment under a scanning electron microscope at a magnification of 1500 times. The oxide layer on the fracture surface falls off, and the original fracture extension path morphology can be observed. The fracture nature is identified as brittle quasi-cleavage, and the oxide layer on the fracture of the P92 seamless steel pipe is removed. The energy spectrum component analysis of the fracture surface after the oxide layer is removed shows that oxygen is added to the alloy elements of the P92 seamless pipe, indicating that the residual oxidation products on the fracture of the P92 seamless pipe after cleaning have no negative impact on the fracture morphology analysis.

[0139] Embodiment 10:

[0140] The method of removing the oxide layer on the fracture of P92 seamless steel pipe can be extended to the removal of the oxide layer on the fracture surface of other steel materials. For example, the removal of the oxide corrosion layer on the fracture surface of cast steel ZG32Mn structural parts includes the following steps:

[0141] Step 1: After the cast steel ZG32Mn sample was placed in anhydrous ethanol and ultrasonically cleaned, it was observed under a scanning electron microscope at 800 times magnification. The original shape of the crack could no longer be recognized.

[0142] Step 2: Prepare and select the cast steel ZG32Mn sample to be analyzed, with a size of 20mm×20mm×10mm. The processing process should ensure that the fracture surface is not damaged and the opposite surface of the fracture should be flat;

[0143] Step 3: Use laser cleaning technology, output power 100W, fiber length 3m, cleaning scan width 20mm, aim the laser cleaning machine scanning head at the P92 sample fracture oxide layer scanning for 60 seconds, so that the oxide layer on the sample surface falls off and the sub-surface becomes loose. The laser-cleaned P92 sample is placed in anhydrous ethanol solution for ultrasonic vibration mechanical cleaning to ensure that there is no residual attachment on the sample surface.

[0144] Step 4: Prepare 8% hydrochloric acid aqueous solution, the solute hydrochloric acid is analytical grade, and industrial water can be used. Sodium nitrite corrosion inhibitor is added to the hydrochloric acid solution, and the volume ratio of sodium nitrite to hydrochloric acid is 1:4. Pour the hydrochloric acid solution into a container, and the hydrochloric acid liquid level is 14mm;

[0145] Step 5: Prepare the sample holder, fix the cast steel ZG32Mn sample on the holder with the fracture surface facing downwards. The vertical position of the holder crossbeam is adjustable. Place the vessel containing the hydrochloric acid solution at the center of the bottom of the holder. Adjust the height of the sample so that the oxidized surface of the fracture is completely immersed in the hydrochloric acid solution. Lock the limit switch of the holder to fix it.

[0146] Step 6: After the oxidized surface of the fracture of the cast steel ZG32Mn sample has been immersed in the solution for 6 hours, observe the color of the hydrochloric acid solution. When the solution turns light blue, the sample can be removed, otherwise it will be immersed further;

[0147] Step 7: Remove the cast steel ZG32Mn sample from the bracket, rinse with water for 1 minute, soak it in acetone solution for 1 hour, take it out of the acetone solution, put it in anhydrous ethanol and clean it with ultrasonic vibration for 10 minutes, and blow it dry;

[0148] Step 8: Observe the fracture morphology of the sample after immersion treatment under a scanning electron microscope at a magnification of 2000 times. The oxide layer on the fracture surface falls off, and the original fracture path morphology can be observed. The fracture nature is identified as brittle cracking along the grain boundary, and the oxide layer on the fracture of cast steel ZG32Mn is removed.

[0149] The terms used in the present invention are illustrative and exemplary, rather than restrictive. Since the present invention can be implemented in various forms without departing from the spirit or essence of the technical solution, it should be understood that the above embodiments are not limited to any of the aforementioned details, but should be widely interpreted within the spirit and scope defined by the attached claims, so all changes and modifications falling within the scope of the claims or their equivalents should be covered by the attached claims.

Claims

1. A method for removing the oxide layer on the crack fracture of a P92 seamless steel pipe, characterized in that: include: Select the P92 crack fracture sample to be analyzed, the size of which should not exceed 60mm×60mm× 30mm, the fracture surface is not damaged, and the upper and lower parallel surfaces of the fracture should be flat; Laser cleaning technology is used. The scanning head of the laser cleaning machine is aimed at the oxide layer of the fracture of the P92 sample to scan, so that the oxide layer on the surface of the sample falls off and the sub-surface becomes loose. Prepare a hydrochloric acid solution with a volume ratio of 5%-10%; the solute hydrochloric acid is analytical grade with a mass fraction of 36%-38%, industrial water can be used, and sodium nitrite corrosion inhibitor is added to the hydrochloric acid solution, the volume ratio of sodium nitrite corrosion inhibitor to hydrochloric acid is 1:3-1:5, and the hydrochloric acid solution is poured into an acid-resistant container; Fix the oxidized fracture surface of the laser-cleaned P92 sample on the bracket with the surface facing downward, place the vessel containing the hydrochloric acid solution at the center of the bottom of the bracket, adjust the height of the sample so that the oxidized surface of the fracture is completely immersed in the hydrochloric acid solution for 5 to 10 hours, and observe the color of the hydrochloric acid solution until the solution turns light blue; After soaking, remove the P92 seamless pipe sample from the bracket, rinse with water for 1 minute to 2 minutes, soak in acetone solution for 0.5 hour to 1 hour, take out the sample from the acetone solution, put it in anhydrous ethanol and clean it with ultrasonic vibration for 5 minutes to 10 minutes, and blow dry.

2. The method for removing the oxide layer on the crack fracture of P92 seamless steel pipe according to claim 1, characterized in that: Laser cleaning technology is used, with an output power of 50W-100W, an optical fiber length of 3-5m, a cleaning scan width of 10mm-100mm, and the laser cleaning machine scanning head is aimed at the oxide layer of the P92 sample fracture and scanned for 30 seconds to 60 seconds, so that the oxide layer on the surface of the sample falls off and the sub-surface layer becomes loose.

3. The method for removing the oxide layer on the crack fracture of P92 seamless steel pipe according to claim 1, characterized in that: The volume concentration of the hydrochloric acid solution is 8%, the corrosion inhibitor is the cleaning product detergent, the sample is immersed for 6 hours, and the cross section is immersed 3mm below the liquid surface of the hydrochloric acid solution. The immersion process is best carried out in a ventilated kitchen, and a small amount of hydrochloric acid solution will evaporate during the immersion process.

4. The method for removing the oxide layer on the crack fracture of P92 seamless steel pipe according to claim 1, characterized in that: The concentration of hydrochloric acid aqueous solution is 10%, the soaking time is 6 hours, the water rinse is 1.5 minutes, the acetone soak is 1 hour, and the alcohol ultrasonic vibration cleaning is 10 minutes.

5. The method for removing the oxide layer on the crack fracture of P92 seamless steel pipe according to claim 1, characterized in that: After laser cleaning technology is used to thin and loosen the oxide layer, hydrochloric acid solution is used to react electrochemically with the metal surface oxide to produce Cl - The ion products are dissolved in the test solution, reducing the Cl- ion products attached to the metal surface. The dissolution reaction time is controlled under the action of the corrosion inhibitor sodium nitrite in the dissolving solution, so that the dissolution reaction occurs slowly, and the oxide on the metal surface is gradually peeled off. At the same time, excessive reaction of the original metal at the bottom of the oxide layer with the acid solution is avoided, and the original morphology of the metal fracture surface is retained.

6. The method for removing the oxide layer on the crack fracture of P92 seamless steel pipe according to claim 1, characterized in that: Pour the hydrochloric acid solution into an acid-resistant container with a liquid level of 15mm-20mm to ensure that the fracture surface of the P92 specimen is in full contact with the solution.

7. The method for removing the oxide layer on the crack fracture of P92 seamless steel pipe according to claim 1, characterized in that: Place the vessel containing the hydrochloric acid solution at the center of the bottom of the bracket, adjust the height of the sample so that the oxidized surface of the fracture is completely immersed in the hydrochloric acid solution, and lock the bracket limit switch to fix it.

8. The method for removing the oxide layer on the crack fracture of P92 seamless steel pipe according to claim 1, characterized in that: The secondary electron mode of the scanning electron microscope was magnified 1000 times to observe the secondary cracks, metallurgical and casting defects of the fracture after cleaning, and the causes of the fracture were analyzed.

9. The method for removing the oxide layer on the crack fracture of P92 seamless steel pipe according to claim 1, characterized in that: The wire cutting method is used to take samples vertically along the fracture surface after the oxide layer is removed. After grinding and polishing, the inspection surface reaches a mirror state, and it is ensured that the edges connected to the fracture surface have no chamfers. The thickness of the residual oxide layer on the edges is measured by observation with a microscope at 500 times.

10. The method for removing the oxide layer on the crack fracture of P92 seamless steel pipe according to claim 1, characterized in that: The laser output power was 80W, the optical fiber length was 3m, the cleaning scanning width was 50mm, and the scanning head of the laser cleaning machine was aimed at the oxide layer of the fracture of the P92 sample for 45 seconds.

Citation Information

Patent Citations

  • Laser-electric arc composite cleaning method for aluminum alloy oxide film

    CN116727862A

  • Treatment device and method for severe corrosion pollution failure fracture

    CN117798136A

  • Rust fracture cleaning liquid as well as preparation method and application thereof

    CN118127519A

  • Metal matrix surface cleaning method based on soluble salt laser composite action

    CN119076492A

  • Method and apparatus for treating a surface, in particular in order to free it of impurities

    WO2007080102A1